2020
DOI: 10.1101/2020.04.01.020495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RDoC Mechanisms of Transdiagnostic Polygenic Risk for Trajectories of Depression: From Early Adolescence to Adulthood

Abstract: There is substantial heterogeneity in the development of depression across early adolescence into adulthood. Yet, little is known about the risk factors underlying individual differences in the development of depression. For instance, despite the discovery of genetic variants for depression, there is also significant genetic overlap between depression and other mental disorders. Thus, depression may have etiologically complex (i.e., transdiagnostic) origins when accounting for its heterogeneous developmental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The issue of whether or not psychiatric PGS models can be made to be more developmentally sensitive is critical to address in future studies, as emerging studies have shown that psychiatric PGS may be better in predicting certain trajectories of psychopathology over others (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of whether or not psychiatric PGS models can be made to be more developmentally sensitive is critical to address in future studies, as emerging studies have shown that psychiatric PGS may be better in predicting certain trajectories of psychopathology over others (38).…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential for confounding due to mixed-informant effects (i.e., adult self-report vs. parent-report of children’s psychiatric disorders), as well as the limited power to detect effects in the adult subsamples for PNC and SPARK, we limited our PGS association analyses to children. The issue of whether or not psychiatric PGS models can be made to be more developmentally sensitive is critical to address in future studies, as emerging studies have shown that psychiatric PGS may be better in predicting certain trajectories of psychopathology over others (38).…”
Section: Discussionmentioning
confidence: 99%
“…The empirical articles in this special section highlight key strengths of the developmental psychology research tradition, including the use of multiple informants (e.g., Liu et al, 2022), longitudinal designs (e.g., Li et al, 2022), and multiple-measure assessments of key constructs. Although we appreciate that not every biobehavioral study of psychopathology can afford to implement each of these strategies, the manifestation of psychopathology over the life span shows remarkable diagnostic heterogeneity and transitions among the spectra (internalizing, externalizing, and thought problems; Caspi et al, 2020).…”
Section: The Importance Of Measurement and Assessment Inmentioning
confidence: 99%
“…We examine this agenda from the perspective of another modern approach to psychiatric classification: the Hierarchical Taxonomy of Psychopathology (HiTOP; Kotov et al, 2017). Building on four of the contributions to this special section (Damme et al, 2022;Li et al, 2022;Liu et al, 2022;Petersen & LeBeau, 2022), we highlight three areas for advancing developmental integration within broadband psychiatric frameworks: (a) the importance of structural models of personality and psychopathology, (b) the value of improving measurement and assessment, and (c) the opportunities offered to such frameworks by stronger integration of developmental context. We articulate ways in which the HiTOP model advances our understanding of mental health and its development beyond the RDoC approach, as well as areas in which developmental integration is lacking in both HiTOP and RDoC frameworks.…”
mentioning
confidence: 99%
“…Li et al (2022) embrace the emphasis of the RDoC framework on transdiagnostic processes in their examination of associations between a polygenic score (PGS) for general psychopathology (the p factor) and multiple RDoC dimensions, including negative emotionality (an index that spans acute threat, potential threat, sustained threat, loss, and frustrative nonreward, the negative valence domain constructs), novelty seeking (an index of reward responsiveness, a positive valence domain construct), and picture vocabulary (an index of language, a cognitive domain construct), measured using self-report questionnaires and performance on a neurocognitive test. They find that the transdiagnostic PGS predicted depression trajectories during the transition from adolescence into early adulthood, as well as suggestive evidence of a specific indirect association for negative emotionality (but not novelty seeking or picture vocabulary).…”
Section: Psychopathological Processes As Dynamic Rather Than Staticmentioning
confidence: 99%